Spectroscopic, electrochemical and photovoltaic properties of Pt(II) and Pd(II) complexes of a chelating 1,10-phenanthroline appended perylene diimide - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (ROYAL SOC CHEMISTRY, 2018)
In this study, a bis-chelating bridging perylene diimide ditopic ligand, namely N,N'-di(1,10-phenanthro-line)-1,6,7,12-tetrakis-(4-methoxyphenoxy)perylene tetracarboxylic acid diimide (1), was synthesized and characterized. Further reactions of 1 with d(8) metal ions such as Pt(II) and Pd(II) having preferential square-planar geometry afforded the novel triads [(Cl-2) M(II)-(1)-M(II)(Cl-2)] where M(II) = Pt(II) (2), and Pd(II) (3), respectively. The isolated triads and the key precursor were fully characterized by FT-IR, 1D-NMR (H-1 NMR and C-13 DEPT NMR), 2D-NMR (H-1-H-1 COSY, H-1-C-13 HSQC, H-1-C-13 HMBC), MALDI-TOF mass and UV/Vis spectroscopy. The electrochemical properties of 1, 2 and 3 were investigated by cyclic voltammetry as well as in situ spectroelectrochemistry and also in situ electrocolorimetric measurements. These compounds were shown to exhibit net colour changes suitable for electrochromic applications. The compounds exhibited remarkably narrow HOMO-LUMO gaps, leading to their ease of reduction at low negative potentials. More importantly, dye-sensitized solar cells (DSSCs) were also fabricated using 1-3 to clarify the potential use of these complexes as a sensitizer. Analysis of the experimental data indicated that 2 has good potential as a sensitizer material for DSSCs.
Keywords: SENSITIZED SOLAR-CELLS; ORGANIC SEMICONDUCTORS; ENERGY CONVERSION; BISIMIDE DYES; PLATINUM(II); PERFORMANCE; ACID; POLYMERIZATION; ELECTRONICS; FLUORESCENT